UKRAINIAN ARTISTIC DOCUMENTARY LITERATURE ABOUT THE EVENTS OF THE FIRST WORLD WAR - Tovt, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
Purpose of the article. In Ukrainian literature about the events of the First World War, in addition to fictional works, there exists a rather significant layer of documentary writing – diary entries, memoirs, journalistic articles, recollections, notes, confessions, and other genre forms. The task of researching them is a specific and important mission for contemporary literary scholars and historians. These diverse literary materials contain both subjective and objective facts, phenomena, and processes recorded by writers and eyewitnesses of the wartime hardships of the early 20th century. In accordance with the aim and objectives of the article, the methodology used includes: historical-cultural, biographical, hermeneutic, and comparative-typological methods. As a result of the research, the ideological and aesthetic features of Ukrainian documentary writing about the First World War have been identified; diary entries and memoirs of a number of Ukrainian authors – both from mainland Ukraine and the diaspora – have been analyzed; and the unique poetics of such works have been examined. This constitutes the scientific novelty of the proposed study. Moreover, the study has practical value, as these materials can be used in Ukrainian literature classes in modern Ukrainian schools, in higher education institutions, and in literary and historical research related to the events of the First World War.